Brain Edema Formation and Functional Outcome After Surgical Decompression in Murine Closed Head Injury Are Modulated by Acetazolamide Administration - Szczygielski, Jacek; Hubertus, Vanessa; Kruchten, Eduard; Müller, Andreas; Albrecht, Lisa Franziska; Mautes, Angelika E.; Schwerdtfeger, Karsten; Oertel, Joachim (Frontiers in Neurology, 2019)
Acetazolamide (ACZ), carbonic anhydrase inhibitor, has been successfully applied in several neurosurgical conditions for diagnostic or therapeutic purposes. Furthermore, neuroprotective and anti-edematous properties of ACZ have been postulated. However, its use in traumatic brain injury (TBI) is limited, since ACZ-caused vasodilatation according to the Monro-Kellie doctrine may lead to increased intracranial blood volume / raise of intracranial pressure. We hypothesized that these negative effects of ACZ will be reduced or prevented, if the drug is administered after already performed decompression. To test this hypothesis, we used a mouse model of closed head injury (CHI) and decompressive craniectomy (DC). Mice were assigned into following experimental groups: sham, DC, CHI, CHI+ACZ, CHI+DC and CHI+DC+ACZ (n=8 each group). 1d and 3d post injury, the neurological function was assessed according to Neurological Severity Score (NSS) and Beam Balance Score (BBS). At the same time points, brain edema was quantified by MRI investigations. Functional impairment and edema volume were compared between groups and over time. Among the animals without skull decompression, the group additionally treated with acetazolamide demonstrated the most severe functional impairment. This pattern was reversed among the mice with decompressive craniectomy: CHI+DC treated but not CHI+DC+ACZ treated animals showed a significant neurological deficit. Accordingly, radiological assessment revealed most severe edema formation in the CHI+DC group while in CHI+DC+ACZ animals, volume of brain edema did not differ from DC-only animals. In our CHI model, the response to acetazolamide treatment varies between animals with decompressive craniectomy and those without surgical treatment. Opening the cranial vault potentially creates an opportunity for acetazolamide to exert its beneficial effects while vasodilatation-related risks are attenuated. Therefore we recommend further exploration of this potentially beneficial drug in translational research projects.